PHOTODYNAMIC THERAPY OF RESIDUAL LARYNGEAL TUMOR AFTER EBRT (CASE REPORT) - V. M. Legostaev; G. M. Maldonado; E. F. Islamova (Biomedical Photonics, 2017)
A case of successful photodynamic therapy of residual laryngeal tumor after external beam radiotherapy (EBRT) is reported. The female patient with diagnosis of laryngeal cancer T1N0M0 underwent a course of EBRT on larynx, fraction dose = 2 Gy, 5 fractions per week, total radiation dose = 60 Gy. One month after EBRT the continued growth of residual tumor in the left vocal fold was diagnosed. The patient had 4 courses of photodynamic therapy with photosensitizer fotoditazin at a dose of 100 mg combined with electroresection of residual laryngeal tumor. The control video-assisted laryngoscopy 1 month after the 4th course of photodynamic therapy showed that larynx was flexible, vocal function was fully restored, tumor of the left vocal fold wasn’t detected. Non-recurrence follow-up period is 10 month. The patient is under follow-up.